Development of continuous microbial fuel cell for renewable energy production from wastewater - Hu, Huaining (2009)
There is around 9.5 kJ/L of energy contained in UK wastewater which is wasted through traditional aeration treatment. Microbial fuel cell (MFC) technology provides a new approach to carry the promise of both treating wastewater without aeration and producing renewable energy in the form of electricity and H2. This work has contributed to making this a reality.